Satiety and glycemic control after giving glucomannan-modified growol cookies - Puspaningtyas, Desty Ervira; Sucipto, Adi; Styaningrum, Silvia Dewi; Sari, Puspita Mardika; Nidyarini, Anita; Rahmawati, Dwita Mukti; Lestari, Getha Puji; Sintia, Renata Deby; Ananda, Dhea Putri (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2024)
Background: Obesity has become an epidemic in all parts of the world. One in five deaths is related to obesity predisposition. Providing foods high in fiber can be a solution to treating obesity. The addition of glucomannan to growol cookies can optimize the fiber content of food which will have an effect in controlling satiety and glycemic control.Objective: To study the effect of glucomannan-modified growol cookies, as a healthy snack in the context of preventing obesity, on changes in satiety and blood glucose levels in excessive-weight subjects (ES) and normal-weight subjects (NS).Methods: A quasi-experimental study with a pre-post design without a control group was conducted on 30 subjects (15 NS and 15 ES). The research was carried out at Universitas Respati Yogyakarta in June-July 2023. The satiety test was carried out using the SLIM (Satiety Labeled Intensity Magnitude) method. Blood glucose levels were measured using the Rapid Test method using Easy Touch GCU before, immediately after, and 120 minutes after giving cookies. Data on satiety and blood glucose levels were sequentially analyzed using the Wilcoxon Signed Ranks Test and Paired Samples T Test (comparing before and after intervention) as well as the Mann-Whitney U Test and Independent Samples T Test (comparing between groups) with a significance of 95%.Results: There was a difference in the feeling of fullness between the 0th minute, 30th minute, 60th minute, and 90th minute compared to the initial feeling of fullness (basal) in the entire group (p<0.05). There was no difference in blood glucose levels between fasting blood glucose, 0-minute blood glucose, and 120-minute blood glucose. Glucomannan-modified growol cookies can delay hunger for 1-1.5 hours before the next big meal. Glucomannan-modified growol cookies can also maintain blood glucose stability in the range of 90 mg/dL.Conclusion: Glucomannan-modified growol cookies can have a positive effect on satiety control and glycemic control.